Metacognitive awareness strategies for listening comprehension / Norseha Unin … [et.al.]. - Unin, Norseha; Ch'ng, Looi Chin; Johari, Aiza (2016)
Listening Comprehension is an important component of language learning that requires a great deal of mental activity on the part of the listener (Vandergrift, 1999). It plays a critical role in facilitating language learning as it provides four advantages that include: cognitive, efficiency, utility, and affective advantage (Gary, 1975 as cited in Vandergrift, 1999). Awareness and the use of listening strategies can help students to learn a highly integrative skill for listening comprehension. However, more often than not, language educators have the tendency to focus on reading and writing skills when teaching English as a Second Language. In some cases, listening activities are often carried out as tests or assessments to evaluate the students' abilities for listening comprehension, which may lead to anxiety and apprehension (Vandergiff, 1999). When students are faced with difficulty in listening tasks, their anxiety and apprehension may cause high failure rates in listening assessments. The deficiency in the development of listening skills would negatively influence the students' reading and writing skills (Oxford, 1993; Vandergiff, 1997).